Implementation of Authentic Assessment of Islamic Religious Education in the Merdeka Curriculum: Qualitative Studies in the Cognitive, Affective, and Psychomotor Domains in Vocational High Schools - Aisyah Aisyah; Saona Saona; Sayed Habibullah Sadaat (Publikasi Indonesia, 2024)
The implementation of the Merdeka Curriculum requires an authentic Pendidikan Agama Islam (PAI) assessment that evaluates learning outcomes holistically while providing feedback for learning improvement. The objectives of this study are (1) to describe the implementation of authentic PAI assessments in the cognitive, affective, and psychomotor domains in vocational schools; (2) to analyze the role of the Merdeka Curriculum in improving PAI learning quality through feedback and measurement of learning objectives; and (3) to reveal the dynamics of test and non-test techniques across all three domains, including the challenges, strategies, and best practices of educators in implementing authentic assessments. This study employed qualitative research with a case study design. Data were collected through interviews, learning observations, and documentation of teaching materials and assessment artifacts, then analyzed through data reduction, presentation, and conclusion drawing, accompanied by triangulation of sources and techniques. Cognitive assessment was carried out through written and oral tests and assignments; the affective domain through observation, attitude journals, self-assessment, and peer assessment; and the psychomotor domain through worship practice demonstrations and performance rubrics. The Merdeka Curriculum strengthens formative assessment and constructive feedback as a basis for remedial and enrichment activities and the adjustment of teaching strategies, while summative assessment maps the achievement of learning objectives and informs planning for the next cycle. Authentic PAI assessment in the Merdeka Curriculum improves learning quality through the integration of the three domains, the use of rubrics, and continuous feedback that drives process improvement and the achievement of learning objectives.